Adapting Beyond Educational Background: Self-Adjustment Strategies of Workers in Nonlinear Careers - Saputri, Devita Dwi; Muntafi, Muhammad Syifaul (International Conference on Sustainable Health Promotion, 2025)
Self-adjustment in the workplace becomes a challenge for individuals working outside their field of study. This study aims to understand the experiences of workers adapting to jobs unrelated to their educational backgrounds. In-depth interviews and observations were conducted with two early adult female participants whose educational backgrounds differ from their work fields. Data were analyzed using a qualitative approach with phenomenology. The study results identified five key dimensions of self-adjustment: accurate perception of reality, stress and anxiety management, positive self-image, emotional expression, and interpersonal relationships. Strategies such as self-directed learning, emotional management through spiritual approaches or relaxation activities, effective communication building, and social support from the work environment proved helpful for participants in adapting to their jobs. This research provides insights for companies to create a supportive work environment that fosters employee development.